2011
DOI: 10.1007/s12275-011-0268-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characteristics of tunisian isoniazid-resistant Mycobacterium tuberculosis strains

Abstract: Forty three isoniazid (INH)-resistant Mycobacterium tuberculosis isolates were characterized on the basis of the most common INH associated mutations, katG315 and mabA -15C→T, and phenotypic properties (i.e. MIC of INH, resistance associated pattern, and catalase activity). Typing for resistance mutations was performed by Multiplex Allele-Specific PCR and sequencing reaction. Mutations at either codon were detected in 67.5% of isolates: katG315 in 37.2, mabA -15C→T in 27.9 and both of them in 2.4%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…This showed that the possible transmission of strains with a similar type of target gene of specific mutations in the community. In contrast to this study, however, in which, mutations in InhA gene was not occurred in any of our isolates, a high and low level of frequency of inhA mutation was reported in Tunisia and Canada [25] , [26] .…”
Section: Discussioncontrasting
confidence: 99%
“…This showed that the possible transmission of strains with a similar type of target gene of specific mutations in the community. In contrast to this study, however, in which, mutations in InhA gene was not occurred in any of our isolates, a high and low level of frequency of inhA mutation was reported in Tunisia and Canada [25] , [26] .…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were reported from the studies conducted in Spain 15 and Myanmar 28. In contrast to this study, high and low level of frequency of inhA mutation was reported from Tunisia 36.1% 29, Canada 26% 30 .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are quite consistent with the world literature confirming katG gene Ser315 → Thr replacement to be the most prevalent (88.6%) [ 19 , 28 – 31 ]. On the contrary, they found relatively lower katG gene mutations prevalence (less than 40%) in RIF-resistant strains of Mycobacterium tuberculosis in Tunisia [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%